Polymersomes Based Versatile Nanoplatforms for Controlled Drug Delivery and Imaging - Rohini Kotha; Divya Dhatri Kara; Rajeshwari Roychowdhury; Katikala Tanvi; Mahalaxmi Rathnanand (Tabriz University of Medical Sciences, 2023)
Drug delivery systems made based on nanotechnology represent a novel drug carrier system that can change the face of therapeutics and diagnosis. Among all the available nanoforms polymersomes have wider applications due to their unique characteristic features like drug loading carriers for both hydrophilic and hydrophobic drugs, excellent biocompatibility, biodegradability, longer shelf life in the bloodstream and ease of surface modification by ligands. Polymersomes are defined as the artificial vesicles which are enclosed in a central aqueous cavity which are composed of self-assembly with a block of amphiphilic copolymer. Various techniques like film rehydration, direct hydration, nanoprecipitation, double emulsion technique and microfluidic technique are mostly used in formulating polymersomes employing different polymers like PEO-b-PLA, poly (fumaric/sebacic acid), poly(N-isopropylacrylamide) (PNIPAM), poly (dimethylsiloxane) (PDMS), and poly(butadiene) (PBD), PTMC-b-PGA (poly (dimethyl aminoethyl methacrylate)-b-poly(l-glutamic acid)) etc. Polymersomes have been extensively considered for the conveyance of therapeutic agents for diagnosis, targeting, treatment of cancer, diabetes etc. This review focuses on a comprehensive description of polymersomes with suitable case studies under the following headings: chemical structure, polymers used in the formulation, formulation methods, characterization methods and their application in the therapeutic, and medicinal filed.